On a Limit of Perturbed Conservation Laws with Diffusion and Non-Positive Dispersion - Bedjaoui, Nabil (2017)
We consider a conservation law perturbed by a linear diffusion and a general form of non-positive dispersion. We prove the convergence of the corresponding solution to the entropy weak solution of the hyperbolic conservation law.